Canalization acoustic phonon polaritons in metal-MoO3-metal sandwiched structures for nano-light guiding and manipulation. (4th January 2022) - Yan, Qizhi; Chen, Runkun; Yuan, Zhu; Li, Peining; Zhang, Xinliang
Abstract: We theoretically propose and study in-plane anisotropic acoustic phonon polaritons (APhPs) based on a layered structure consisting of a monolayer (or few layers) α -phase molybdenum trioxide ( α -MoO3 ) sandwiched between two metal layers. We find that the APhPs in the proposed sandwiched structures are a canalization (highly directional) electromagnetic mode propagating along with the layers and at the same time exhibit extreme electromagnetic-field confinement surpassing any other type of phonon-polariton modes. When a double layer of α -MoO3 is sandwiched by two Au layers, twisting the two α -MoO3 layers can adjust the interlayer polaritonic coupling and thus manipulate the in-plane propagation of the highly confined APhPs. Our results illustrate that the metal-MoO3 -metal sandwiched structures are a promising platform for light guiding and manipulation at ultimate scale.